2016
DOI: 10.1097/qai.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dolutegravir on the Pharmacokinetics of Metformin in Healthy Subjects

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 18 publications
2
77
0
1
Order By: Relevance
“…A similar magnitude DDI has also been reported with another antibiotic, cephalexin . Recently, Zong et al reported that the antiretroviral drug dolutegravir caused the largest DDI with metformin reported to date, increasing metformin's C max and AUC by up to 2.11‐ and 2.45‐fold, respectively, after twice‐daily dolutegravir administration . The mechanism of the interaction appears to be the potent inhibition of the organic cation transporter 2 (OCT2, SLC22A2) by dolutegravir …”
Section: Commonly Prescribed Victim Drugssupporting
confidence: 52%
“…A similar magnitude DDI has also been reported with another antibiotic, cephalexin . Recently, Zong et al reported that the antiretroviral drug dolutegravir caused the largest DDI with metformin reported to date, increasing metformin's C max and AUC by up to 2.11‐ and 2.45‐fold, respectively, after twice‐daily dolutegravir administration . The mechanism of the interaction appears to be the potent inhibition of the organic cation transporter 2 (OCT2, SLC22A2) by dolutegravir …”
Section: Commonly Prescribed Victim Drugssupporting
confidence: 52%
“…Efficient phagocytosis and proper adaptive immune priming are necessary to activate cell-mediated immune responses that restrict M. tuberculosis growth, and delayed or altered responses likely contribute to diabetic TB susceptiblity 11 . Diabetic individuals with LTBI have lower frequencies of M. tuberculosis-specific pro-inflammatory (Th1 and Th17), anti-inflammatory (IL-10) and Th2 responses compared to normoglycemic individuals with LTBI 12,13 . The IL-20 family of cytokines is also lower in LTBI-DM whereas IL-22 is higher 14 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…11,12 Other minor biotransformation pathways include oxidation by cytochrome P450 3A4 and metabolism by UGT1A3 and UGT1A9. 15 Dolutegravir is also a substrate for P-glycoprotein and breast cancer resistance protein in vitro. Dolutegravir also potently inhibits the organic cation transporter 2 12 and multidrug and toxin extrusion 1 transporter.…”
mentioning
confidence: 99%